RECOMMENDED TACTICS FOR THE EVALUATION OF POTENTIALLY MALIGNANT DISORDERS IN THE ORAL CAVITY - S.V. Kolomiiets; K.O. Udaltsova; V.I. Shynkevych (Ukrainian Medical Stomatological Academy, 2018)
Since oral cavity, head and neck are relatively well-visualized anatomical sites, the dentists have multifold possibilities for the evaluation of the oral mucosa, face skin, lips, and neck lymph nodes during their routine work. Dentists are the specialists who are able to detect malignant tumors and refer patients to the oncologists. The aim of the article is to compare the clinical recommendations of the Ministry of Healthcare of Ukraine and the recommendation made by the American Dental Association (ADA) in their updated clinical practice guidelines for the evaluation of potentially malignant disorders in the oral cavity. Basic principles of the oncological alertness in dentistry, and the route organization of clinical patient. The usage of the classification of precancerous diseases, proposed by Ye.V. Borovskyi, M.F. Danilevskyi, A.L. Mashquillain (1991) is the first step of the oncological alertness in dentistry. The role of dentist is adjuvant and helps to identify a suspicious oral lesion. A pattern of action in such situations is referring patients directly to an oncologist, who will conduct a biopsy, histological examination and treat the cancer. Consequently, the attention of Ukrainian dentists is focused on precancerous lesions, but less attention is paid actually to the cancer. Responsibility for dispanserisation (clinical follow up) is carried mainly by dentists-surgeons without participation of orthopedists, pediatric dentists, and orthodontists. Those involve whole series of redirections of the patient among dentists themselves, before referring to the really necessary specialist, and it represents a negative item in the organization. In contrast to the algorithm provided by the Ministry of Healthcare of Ukraine, doing an immediate biopsy in patients with a suspicious oral lesion - or referring a patient to a specialist who can do that - remains the only most important recommendation made by the American Dental Association (ADA) in their updated clinical practice guidelines for the evaluation of potentially malignant disorders in the oral cavity. Epidemiological data in Ukraine, unlike the USA, is not enough to understand the real situation and to plan the measures of oncological alertness. Risk factors for malignant lesions in the oral cavity. The role of HPV-related cancer of the oral cavity is underestimated in Ukraine. "Over the past 20 years HPV infection has surpassed tobacco and alcohol as a major risk factor [for head and neck cancer]," the ADA authors note, and they estimate that HPV infection causes approximately 75% of all OPSCCs identified today.  Adjunctive test for precancerous and cancerous cases in the oral cavity (include autofluorescence, tissue reflectance, vital staining, and salivary adjuncts) is recognized by the Ukrainian and American experts, as "adjuncts", none of which was felt to be accurate enough to identify target lesions in the primary care setting. These methods do not exceed the accuracy of the histological examination. Conclusions. Regardless the geography, dentists have a good opportunity to assess patients for oral cancer caused by traditional head and neck risk factors. Dentists of Ukraine have a good opportunity at the primary care setting to get reports about head and neck cancer prevention, and to inform their patients. The clinical route of a patient with suspected oral lesions is flexible and is connected with appropriate consulting centers, which facilitates the activity of a dentist, but creates additional redirections instead of referring to the specialist immediately. Ukrainian dentists should take signs of HPV-related cancer - cancer that occur at the back of the throat, at the base of the tongue, and on the tonsils - are difficult if not impossible to visualize. So dentists must be trained not only to look inside the mouth but also to assess patients for tonsillar asymmetry.